Inteligencia artificial y sistemas biométricos de uso militar: redefinir la inteligencia artificial desde la ética y el derecho (Journal of the Spanish Institute for Strategic Studies, 2025)
This article addresses the need to prevent without limiting or doing what is fair, so that AI as an almost plenipotentiary tool contributes its immense grain of sand in security and defense applications. In particular, the use of biometric systems represents a whole world of opportunities in the security sector, but at the same time it confronts inalienable rights and guarantees. This situation of confrontation must be resolved from the point of view of ethics and law, without in any case determining an absolute limit to the use of a decisive tool, with basic and essential military applications.
Keywords: Artificial intelligence, military applications, biometric, ethic, limits, laws.